Effects of seed preparation with gibberellic acid and brassinosteroid on germination indices and physiological traits after accelerated aging - Saeed Moori; Hamid Reza Eisvand; Ahmad Ismaili; Shahryar Sasani (علوم و فناوری بذر ایران)
Germination and seedling production have an important role in crop production. This stage is influenced by quality of the seed strongly. Seed priming with gibberellic (GA3 100 ppm) acid and brassinosteroid (BR 100 ppm) on deteriorated wheat (Triticum aestivum. L) seeds were studied. A factorial experiment based on a completely randomized design with three replications was conducted in 2016. Treatments were seed aging (non-aged and accelerated aged) and seed pretreatment with GA3 and BR. No priming and hydro priming also were used as controls. Analysis of variance showed that the interaction of accelerated aging and priming was significant for germination percentage, plumule length, R/P L, germination rate, MDG, and GI; and for radicle length, DGS and CVG at 5% level. However, on the seedling length and mean germination time was not significant. The results showed that accelerated aging significantly reduced the soluble protein in seedlings and in turn caused a significant increase in malondialdehyde, soluble sugar, and proline content. The results showed that, the germination characteristics were improved under GA3 treatment.